PENGELOLAAN KREATIVITAS DAN INOVASI MELALUI INTEGRASI SENI DAN TEKNOLOGI DALAM PENDIDIKAN DI ERA DIGITAL 5.0 - Cahyaningrum, Yuniana; Ramdhani, Dani Eka; Istiqomah, Asyifa’ Nur; Noviyanti, Nikita (Jurnal AbdiMas Nusa Mandiri, 2025)
The development of digital technology has brought significant changes in various aspects of life, including in the world of education. The integration of art and technology is an important strategy in facing challenges and opportunities in the digital era 5.0, especially in efforts to increase creativity and innovation among students. This community service work aims to develop a learning model that combines elements of art and technology, in order to enrich the learning experience and prepare the younger generation to be actively involved in an increasingly digital and creative society. Through training programs and workshops, educators and students are introduced to various digital tools and platforms that can be used to create works of art, ranging from graphic design, animation, to digital music. In addition, the application of technologies such as Augmented Reality (AR) and Virtual Reality (VR) in art education is also introduced as an innovative way to increase understanding and appreciation of art. The results of this activity show a significant increase in students' ability to think creatively and produce innovative works. Students also show a higher interest in project-based learning that integrates technology, which has a positive impact on their engagement in the learning process. This publication provides an overview of best practices and challenges in implementing the integration of art and technology in the world of education, as well as recommendations for further development.